Studying the Earth with Geoneutrinos - L. Ludhova; S. Zavatarelli (Advances in High Energy Physics)
Geoneutrinos, electron antineutrinos from natural radioactive decays inside the Earth, bring to the surface unique information about our planet. The new techniques in neutrino detection opened a door into a completely new interdisciplinary field of neutrino geoscience. We give here a broad geological introduction highlighting the points where the geoneutrino measurements can give substantial new insights. The status-of-art of this field is overviewed, including a description of the latest experimental results from KamLAND and Borexino experiments and their first geological implications. We performed a new combined Borexino and KamLAND analysis in terms of the extraction of the mantle geo-neutrino signal and the limits on the Earth's radiogenic heat power. The perspectives and the future projects having geo-neutrinos among their scientific goals are also discussed.